Cooperative Learning Model Type of Index Card Match Against Science Learning Outcomes in Elementary School - Zulherman (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the effect of science learning outcomes by using the Cooperative Learning Model Index Card Match type in fourth-grade students of SDN Jatiwaringin III Pondok Gede in semester 2 of the 2018-2019 school year. The research method used is a quantitative method with a Posttest-Only Control Design research design. The sampling used in this study is the Non-Probability sampling technique, which is saturated sampling. In the validity test using Point Biserial Correlation as many as 50 questions. Data were analyzed using the normality requirements test using the Liliefors test obtained in the experimental class Lo 0.14